2013
DOI: 10.1590/1679-775720130091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the intercanine distance in newborns with cleft lip and palate using 3D digital casts

Abstract: ObjectiveThe purpose of this present study was to compare, by means of 3D digital casts, the anterior transverse dimension of the dental arch of newborns with and without cleft lip and palate.Material and MethodsThe sample was composed of ninety-four children aged from 3 to 9 months divided into three study groups: Group I - children without craniofacial deformities (control group); Group II - children with unilateral cleft lip and palate; Group III - children with bilateral cleft lip and palate. Impressions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 16 publications
2
25
1
13
Order By: Relevance
“…Relative maxillary arch constriction results from scarring due to primary surgery [22] and an intrinsic growth deficiency in patients with CLP. [23] The present study identified non-significant growth differences between two cleft types regarding relative maxillary arch constriction, indicating that there is no specific trend of maxillary growth deterioration with time. Nevertheless, subjects with UCLP had a greater degree of relative maxillary arch constriction 7 compared to patients with CP.…”
Section: Discussionmentioning
confidence: 47%
“…Relative maxillary arch constriction results from scarring due to primary surgery [22] and an intrinsic growth deficiency in patients with CLP. [23] The present study identified non-significant growth differences between two cleft types regarding relative maxillary arch constriction, indicating that there is no specific trend of maxillary growth deterioration with time. Nevertheless, subjects with UCLP had a greater degree of relative maxillary arch constriction 7 compared to patients with CP.…”
Section: Discussionmentioning
confidence: 47%
“…Crianças com fissura de lábio e palato completas têm dimensões transversais maiores do que as de crianças sem essa deformidade (FERNANDES et al, 2013).…”
Section: Medidas Transversaisunclassified
“…Porém, após as cirurgias de queiloplastia e palatoplastia, apresentam uma diminuição nessas medidas( MAZAHERI et al, 1971;MELLO et al, 2013; FALZONE et al, 2016 e AMBRÓSIO et al, 2017. Neste estudo, encontrou-se uma alteração na distância transversal anterior (CC'), significantemente menor na maxila do grupo FLPU, condizente com os achados desses autores.…”
unclassified
See 2 more Smart Citations